THE EXISTENCE OF PRIMARY SCHOOL EDUCATION THROUGH THE ROLE OF THE PRINCIPAL: A CASE STUDY IN ELEMENTARY SCHOOL 068/XI KERINCI-JAMBI - Taufik, Taufik; Fadhlan, Muhammad; Fikri, Ahmad; Harisah, Harisah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2023)
This study aims to examine the role of the principal in maintaining the quality of education at State Elementary School (SDN) 068/XI Kerinci, Jambi, focusing on the design, implementation, and evaluation of school management. This research utilizes a descriptive qualitative approach, with the principal as the primary instrument and teachers, students, and parents as supporting instruments. Data collection techniques include observation, interviews, and documentation, while data analysis is conducted through data collection, presentation, condensation, and drawing conclusions. Key findings of this study include: 1) the establishment of the school’s vision and mission, along with the design of intra and extracurricular activities to sustain educational continuity, 2) the appointment of coordinators with subject teachers and extracurricular supervisors to strengthen the existence of education, 3) the provision of rewards and motivation for outstanding teachers and students, positively impacting the sustainability of education, and 4) the implementation of weekly, quarterly, and semester evaluations, which contribute to educational success and student achievement. This study concludes that the principal’s role significantly influences the success of educational institutions in maintaining the existence and quality of education at the elementary school level.